2013
DOI: 10.1186/2049-1891-4-22
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharide enhances immunity and inhibits H9N2 avian influenza virus in vitro and in vivo

Abstract: This study investigated the humoral immunization of Astragalus polysaccharide (APS) against H9N2 avian influenza virus (H9N2 AIV) infection in chickens.The effects of APS treatment on H9N2 infection was evaluated by an MTT [3(4, 5-dimethylthiazol-2-yl)-2, 3-diphenyl tetrazolium bromide] assay and analysis of MHC and cytokine mRNA expression. The effect on lymphocyte and serum antibody titers in vivo was also investigated. IL-4, IL-6, IL-10, LITAF, IL-12 and antibody titers to H9N2 AIV were enhanced in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 23 publications
2
55
1
Order By: Relevance
“…APS, as an effective Chinese medicine extraction from Astragalus, has been shown anti-oxidation, anti-inflammatory, anti-antiviral activity [28]. Most researchers confirmed that APS took antiviral action only by strengthening the immune system [29]. The current work is the first to investigate the effect of APS on PCV2 replication in vitro.…”
Section: Discussionmentioning
confidence: 77%
“…APS, as an effective Chinese medicine extraction from Astragalus, has been shown anti-oxidation, anti-inflammatory, anti-antiviral activity [28]. Most researchers confirmed that APS took antiviral action only by strengthening the immune system [29]. The current work is the first to investigate the effect of APS on PCV2 replication in vitro.…”
Section: Discussionmentioning
confidence: 77%
“…GPS was extracted and purified as described in our previous works [15, 16]. Trizol, isopropanol, chloroform [trichloromethane], DEPC water, and 75% ethanol were used in the extraction of RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Astragalus was used as supplementary forage supplement for livestock and poultry industry in China, because it contains polysaccharides, saponins, flavonoids, anthraquinones, alkaloids, amino acid, β-sitosterol and metallic elements (Ibrahim et al, 2013;Sun et al, 2013;Li et al, 2009). Recent literatures reported that crude extracts of Astragalus are observed to be antiinflammatory (Kim et al, 2013), immunostimulant (Qin et al, 2012), antioxidative (Kim and Yang, 2005), and antiviral in isolated constituents (Kallon et al, 2013). Astragalus was fermented by lactic acid bacteria (LAB) using solid state fermentation (SSF) technology.…”
Section: Introductionmentioning
confidence: 99%